Snap A Pest Tech - Norizuan, Nur Ain; Mohd Zaidi, Intan Syafiqa Aisya; Daud, Muhammad Amir Amirul; Hamizai @ Hamizzi, Mohamad Fariz (2025)
Snap A Pest Tech offers a modern, eco-friendly alternative to traditional pest control through its smart, non-toxic trapping machine designed to safely capture common household and agricultural pests without chemicals. Using natural bait or light-based lures, the device provides a child- and pet-safe solution ideal for homes, food businesses, and farms, delivering portability, durability, and cost-effectiveness. With recyclable materials, low production costs, and strong demand for green, hygienic solutions, Snap A Pest positions itself as a reliable, sustainable choice for modern pest management.